2013
DOI: 10.1002/aqc.2416
|View full text |Cite
|
Sign up to set email alerts
|

The abundance of common bottlenose dolphins (Tursiops truncatus) in the former special marine reserve of the Cres‐Lošinj Archipelago, Croatia

Abstract: There is a resident common bottlenose dolphin population inhabiting the Kvarnerić area of the northern Adriatic Sea, Croatia. The observed decline in population size between 1995 and 2003 led to the declaration of a part of the Kvarnerić as the Cres‐Lošinj Special Marine Reserve (CLSMR) in 2006. Protection lasted 3 years, before lapsing. A boat based photo‐identification study was conducted between 2004 and 2011 with the aim to estimate the number of bottlenose dolphins inhabiting the CLSMR area, investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 27 publications
3
46
0
Order By: Relevance
“…These studies and our data imply a broader, worldwide pattern of small‐scale differentiation for this genus. Photo‐identification data have suggested that common bottlenose dolphins of the Adriatic Sea are structured in putative local populations (Fortuna, ; Genov et al ., , ; Holcer, ; Pleslić et al ., in press), corroborating the results of this study. For instance, in the North Adriatic, no matches were found between individuals from the Gulf of Trieste (Italy, Slovenia and Croatia) and the Kvarnerić archipelago, Croatia, only 120–150 km apart (Genov et al ., , ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies and our data imply a broader, worldwide pattern of small‐scale differentiation for this genus. Photo‐identification data have suggested that common bottlenose dolphins of the Adriatic Sea are structured in putative local populations (Fortuna, ; Genov et al ., , ; Holcer, ; Pleslić et al ., in press), corroborating the results of this study. For instance, in the North Adriatic, no matches were found between individuals from the Gulf of Trieste (Italy, Slovenia and Croatia) and the Kvarnerić archipelago, Croatia, only 120–150 km apart (Genov et al ., , ).…”
Section: Discussionmentioning
confidence: 97%
“…The absence of a clear assignment of individual multilocus genotypes to distinct genetic clusters, despite the Bayesian clustering approach distinguishing five partitions, may be due to limitations of the software in detecting genetic differentiation when F ST values are low (Latch et al ., ). The existence of both resident and visiting individuals, as indicated by photo‐identification studies (Genov et al ., ; Pleslić et al ., ) may be an additional or concomitant cause of why consistent assignment to distinct clusters could not be detected. In particular, a significant proportion of either migrants or individuals of mixed ancestry may result in a degree of gene flow that potentially obscures population structure.…”
Section: Discussionmentioning
confidence: 97%
“…[38, 40, 77, 78]. However, the uncertainty associated to the proportion of unmarked animals is taken into account in the total population estimate because the lower is the mark rate, the higher is the variance [34].…”
Section: Discussionmentioning
confidence: 99%
“…Given bottlenose dolphin movement patterns in and out of the Gulf, our yearly estimates should be interpreted strictly as the number of individuals using the area during the primary occasions and inter-annual variability is unlikely to reflect fluctuations in population size [39]. In other areas, seasonal variations in the abundance of bottlenose dolphins have been related to temporal shift in habitat use, due to factors including reproduction [52], disturbance, and prey availability [23, 40]. Comparisons with photo-identification catalogs from other areas in the Ionian Sea (and beyond) as well as genetic analyses would be needed to investigate population structure [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation